Analysis of colour and polarimetric variability of RW Aur A in 2010–2018. Issue 4 (1st December 2018) - Dodin, A; Grankin, K; Lamzin, S; Nadjip, A; Safonov, B; Shakhovskoi, D; Shenavrin, V; Tatarnikov, A; Vozyakova, O
Abstract: The results of UBVRIJHKLM photometry and VRI polarimetry of a young star RW Aur A observed during unprecedented long and deep (up to Δ V ≈ 5 mag) dimming events in 2010–11 and 2014–18 are presented. The polarization degree p of RW Aur A at this period has reached 30 per cent in the I band. As in the case of UX Ori-type stars (UXORs), the so-called 'bluing effect' in the colour–magnitude V versus V − R c, V − I c diagrams of the star and a strong anticorrelation between p and brightness were observed. However, the duration and the amplitude of the eclipses as well as the value and orientation of the polarization vector in our case differ significantly from those of UXORs. We conclude that the dimmings of RW Aur A occurred due to eclipses of the star and inner regions of its disc by the axisymmetric dust structure located above the disc and created by the disc wind. Taking into account both scattering and absorption of stellar light by the circumstellar dust, we explain some features of the light curve and the polarization degree–magnitude dependence. We found that near the period of minimal brightness the mass-loss rate of the dusty wind was >10 −9 M⊙ yr −1 .